Citizens promote the conservation of flagship species more than ecosystem services in wetland restoration. (October 2017) - Senzaki, Masayuki; Yamaura, Yuichi; Shoji, Yasushi; Kubo, Takahiro; Nakamura, Futoshi
Abstract: Assessing the non-market value of biodiversity conservation is crucial to justify it economically. Using a choice experiment on wetland restoration in Hokkaido, northern Japan, we assessed the willingness of citizens to pay for different ecological statuses of a flagship species (absence, occasional occupancy, permanent occupancy, and breeding) and other principal conservation targets (establishment of a birdwatching station and wetland sizes). The results showed that the fundraising potential of the flagship species surpassed those of other conservation targets, irrespective of its ecological status, highlighting the superior publicity generated by charismatic species. We also showed that upgrading ecological status from occupancy to breeding did not result in additional financial support. Our study emphasizes that, although publicizing ecologically important statuses such as breeding is critical for successful conservation efforts, focusing much effort on flagship species rather than other conservation targets may be important to increase the economic value of conservation practices if such species are available. Graphical abstract: Highlights: Monetary values of three conservation targets were assessed. Monetary value of conservation for a flagship species was the highest. Monetary values of those for wetland size and a birdwatching station were low. Flagship species may be the best target to raise monetary value of conservation.